Characterization based on-street parking management in shopping area of a developing country: A study of Dhaka New Market, Bangladesh - F. Reza; A. N. Kakon; K. A. Asad (Lowland Technology International, 2017)
This study identifies the on-street parking characteristics of Dhaka New Market, a shopping area of Bangladesh. Parking usage survey by patrol was conducted both on weekday and weekend to find out the parking characteristics. The analysis of parking patrol survey data demonstrates that parking accumulation, volume, load and index are much higher at the weekend which indicates raised parking demand than that of weekday. As existing parking supply fail to accommodate higher parking demand spill-over parking is being encouraged and consequently traffic congestion, obstruction to pedestrian movement and bus stop zone have been created. Parking space inventory survey and user opinion survey were also conducted to recognize on-street parking induced problems and to adopt some policy measures in these regards.